Evaluation of Flexural Strength and Hardness of Heat-Cured Acrylic Dentures after Immersion in Ozonated Water and Sodium Hypochlorite Disinfectants: An In Vitro Study - Amirtaher Mirmortazavi; Alireza Chamani; Ahmad Ghahremanloo; vahid salar (Mashhad University of Medical Sciences, 2020)
Introduction: This study aimed to evaluate the effect of various disinfectants on flexural strength and hardness of heat-cured acrylic dentures. Materials and Methods: A total of 60 acrylic samples were prepared with dimensions of 3×10×65 milimeters (30 acrylic Acropars and 30 acrylic Ivoclar). The acrylic samples were immersed into distilled water (control group), as well as sodium hypochlorite 1% and ozonated water (case groups) for 120 minutes. Subsequently, half of the samples were subjected to the flexural strength, and the other half were subjected to the hardness tests. The data were analyzed using 2-way ANOVA and Tukey's test to compare the results. Results: According to the results, there were no significant differences between the samples immersed in the ozonated water and sodium hypochlorite regarding the flexural strength and hardness of acrylic. Conclusion: It seems that flexural strength and hardness of acrylic after immersion in ozonated water and sodium hypochlorite is not affected during the short-term use. Therefore, it is suggested to use ozonated water to disinfect the patient's teeth.